A revision of the genus Pinthaeus (Hemiptera: Heteroptera: Pentatomidae) - Zhao, Qing; Rédei, Dávid; Bu, Wenjun (Zootaxa, 2013)
The genus Pinthaeus Stål, 1868 (Hemiptera: Heteroptera: Pentatomidae: Asopinae) is revised, a single species is recog-nized, redescribed, and illustrated. The following new synonymy is proposed: Pinthaeus sanguinipes (Fabricius, 1781) = P. humeralis Horváth, 1911, syn. nov. A lectotype is designated for P. sanguinipes. The geographic distribution and un-usual intraspecific variability of P. sanguinipes is discussed.